Impact of Regional Emission Distribution of Air Pollutants on Concentration and Population Exposure 대기오염물질의 지역별 배출분포가 농도 및 인구 노출에 미치는 영향 - Park, Junheung; Kim, Eunhye; Kang, Yoon Hee; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2024)
To effectively manage air pollutant emissions, it is crucial to first analyze the impact of emissions on air pollutant concentrations and subsequent human exposure. This study utilized air quality simulations for March 2021, based on top-down emission estimates capable of reproducing observed concentrations of pollutants such as NO2, SO2, and CO in South Korea. The simulated concentrations were further used to calculate the Population Weighted Concentration (PWC). Additionally, a separate simulation was conducted to estimate changes in concentrations and PWC resulting from the removal of regional emission disparities, including emission hotspots. During the study period, the emission density of the top 10% emission hotspots was six times higher for NOx, ten times higher for SO2, and three times higher for CO compared to the national average. These hotspots accounted for 57.5% of the total national NOx emissions, 89.7% of SO2 emissions, and 36.9% of CO emissions. This indicates a high concentration of emissions in specific areas, raising concerns about exceeding air quality standards. Under current emission conditions, NO2 and CO concentrations were highest in the Seoul Metropolitan Area (SMA), while SO2 concentrations were highest in the Chungcheong region. In contrast, the PWC for all three pollutants was the highest in the SMA compared to other regions. Furthermore, the national average PWC for NO2, SO2, and CO was 2.5 times, 2.2 times, and 1.4 times higher, respectively, compared to the national average concentrations. This suggests that, despite improvements in national air quality, relatively high concentrations persist in densely populated areas. In the scenario with flattened emissions, the national average PWC of NO2, SO2, and CO decreased by 50%, 24%, and 23%, respectively. This finding underscores the importance of establishing air quality improvement plans aimed at reducing population exposure within regions, independent of total emission regulations, as strategic siting of emission sources can reduce PWC regardless of regional emission volumes.
Keywords: Air quality simulation; Emission hotspot; Emission management; Population weighted concentration; Regional disparities